E-learning technologies and evidence-based assessment approaches - Spratt, Christine; Lajbcygier, Paul (Advances in information and communication technology education series., 2009)
"This book aims to provide readers with a variety of contemporary solutions to identified educational problems of practice related to the assessment of student learning in e-learning environments"--Provided by publisher.